The Influence of Customer Reviews on Marketplaces on Consumer Trust Using the Systematic Literature Review (SLR) Method - Anggi Sasmita; Suci Suci (International Journal of Economic and Tourism Research, 2025)
In the digital age, customer reviews have become one of the most important factors influencing purchasing decisions. This study aims to analyze the impact of customer reviews on consumer trust levels when conducting transactions on marketplace platforms. The method used in this study is a qualitative approach employing a Systematic Literature Review (SLR). The data utilized are secondary data sourced from relevant research journals and other sources. The results of the study indicate that customer reviews have a positive and significant influence on consumer trust levels in marketplaces. Credible, comprehensive, visual reviews, and those that are well-responded to by sellers are critical factors in building consumer trust. Managing customer reviews should be a strategic priority to enhance loyalty, satisfaction, and the sustainability of transactions in the long term. Therefore, online businesses should actively encourage customers to provide positive reviews by maintaining product and service quality. This finding suggests that sellers need to focus on service quality and encourage customers to provide reviews as a strategy to enhance consumer trust and loyalty.